2012
DOI: 10.1007/s10067-011-1933-9
|View full text |Cite
|
Sign up to set email alerts
|

Refractory multisystem sarcoidosis responding to infliximab therapy

Abstract: Chronic progressive multisystem granulomatous disease is seen in 10-30% of patients with sarcoidosis and can result in end organ damage. Corticosteroids are the mainstay of treatment with the addition of cytotoxic agents in severe cases. Some patients are refractory to such treatment and, therefore, management is a challenge. There is currently limited evidence for biological agents such as infliximab, a monoclonal anti-tumor necrosis factor-α antibody in the treatment of multisystem sarcoidosis. We report out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
2
6
0
1
Order By: Relevance
“…The results of our study are in line with other case series demonstrating efficacy of infliximab in 64-100% of sarcoidosis patients treated [12,30,31]. In the present study, uveitis demonstrated the best response rate (74%), followed by RFI (57%) and SFN (54%).…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study are in line with other case series demonstrating efficacy of infliximab in 64-100% of sarcoidosis patients treated [12,30,31]. In the present study, uveitis demonstrated the best response rate (74%), followed by RFI (57%) and SFN (54%).…”
Section: Discussionsupporting
confidence: 92%
“…There is currently limited evidence for biological agents such as infliximab, a monoclonal anti–TNF α antibody in the treatment of multisystem sarcoidosis [1]. Our case supports the need for randomized controlled clinical trials of anti-TNF therapy in refractory systemic sarcoidosis.…”
Section: Resultssupporting
confidence: 71%
“…Chronic progressive multisystem granulomatous disease is seen in 10–30% of patients with sarcoidosis and can result in end organ damage [1]. Corticosteroids are the mainstay of treatment with the addition of cytotoxic agents in severe cases.…”
Section: Introductionmentioning
confidence: 99%
“…Mainly interferon-c and interleukin-2 are secreted, and TNF-a production is increased through macrophage activation. By analogy with the treatment used in other granulomatous diseases (sarcoidosis, necrobiosis lipoidica), treatment with anti-TNF-a was considered to represent a reasonable option in GA. 5 instances of the treatment of GA with anti-TNF have been reported, including one case with etanercept, 6 four with adalimumab, 7,8 and two with infliximab. 9,10 The present case is remarkable because clinical improvement was observed after one infusion only, and the complete disappearance of lesions was apparent after the fourth infusion.…”
Section: Discussionmentioning
confidence: 99%